International trade of electric vehicle batteries and lithium: a network approach to trade structure and structural inequality - DeBruin, Jacob, author; Roberts, Tony, advisor; Luna, Jessie, committee member; Stevis, Dimitris, committee member (Colorado State University. Libraries, 2023)
As international efforts toward clean energy transition and climate mitigation have been made, the international trade of emission-reducing technologies and their necessary materials has grown. Few technologies have seen as much growth as electric vehicles and their lithium-ion batteries; and few materials have seen as much growth as lithium. Research on international battery and lithium trade is extensive but has yet to examine the formation of the trade structure and its structural inequality. This study uses bilateral trade data from the UN COMTRADE database and country attribute data from the World Bank database to (1) measure the overall structure of and structural inequality in international electric vehicle battery and lithium trade networks; and (2) analyze determinants of the trade networks' formation. Results indicate that the international trade of electric vehicle batteries and of lithium are characterized by a core-periphery pattern—by which certain countries occupy the center of trade, and by which certain countries occupy the margins—and therefore, that there is an inequality in the distribution of trade relationships among countries participating in battery and lithium trade. The results also indicate that differences in countries' GDP and country's structural position in the networks largely determine the likelihood of trade-relationship formation. Inferentially, the results provide some evidence for (ecologically) unequal exchange in the trade of commodities that ostensibly support clean energy transition and sustainable economic development, like electric vehicle batteries and lithium.